2020
DOI: 10.1002/berj.3656
|View full text |Cite
|
Sign up to set email alerts
|

Mapping continuity and change in the intellectual structure of the knowledge base on problem‐based learning, 1974–2019: A systematic review

Abstract: Problem-based learning (PBL) emerged during the 1970s in response to demands for active learning methods capable of developing transferable knowledge and skills in the training of doctors. Over succeeding decades, PBL was gradually adopted in other fields of education. This systematic review aimed to identify key streams of theory and empirical research that have emerged over time in PBL research and practice. The review sourced 12,036 Scopus-indexed documents published between 1974 and 2019. Science mapping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 94 publications
(194 reference statements)
0
13
0
Order By: Relevance
“…For example, because PBL is a form of experiential learning (e.g., Boud & Felletti, 1997;Hmelo-Silver, 2004;Hmelo-Silver et al, 2007;Savery, 2006), educators engaged in PBL research and practice have frequently drawn on theories of experiential (Kolb, 1984), constructivist (Jonassen, 2002), team-based (Johnson & Johnson, 1999) and active learning (Biggs, 2011;Felder & Brent, 2003;Prince & Felder, 2006). Analysis of these interdisciplinary influences on PBL scholarship are further investigated in a companion paper (see Hallinger, 2020).…”
Section: Key Authors In the Pbl Literaturementioning
confidence: 99%
“…For example, because PBL is a form of experiential learning (e.g., Boud & Felletti, 1997;Hmelo-Silver, 2004;Hmelo-Silver et al, 2007;Savery, 2006), educators engaged in PBL research and practice have frequently drawn on theories of experiential (Kolb, 1984), constructivist (Jonassen, 2002), team-based (Johnson & Johnson, 1999) and active learning (Biggs, 2011;Felder & Brent, 2003;Prince & Felder, 2006). Analysis of these interdisciplinary influences on PBL scholarship are further investigated in a companion paper (see Hallinger, 2020).…”
Section: Key Authors In the Pbl Literaturementioning
confidence: 99%
“…This is probably due to the teaching and learning methodology's historical origin and field of development, which started in MacMaster University in the late 1960s [7], where medical students were able to memorize information but lacked the development of clinical skills to diagnose a patient with an authentic problem [11]. So, PBL as an active learning method emerged to develop transferable knowledge and skills in medical school [20]. Nevertheless, although this learning method can be successfully applied to science, technology, engineering and mathematics (STEM) areas [21], and it is also viewed as a pedagogy that promotes science literacy among students [12], there is less focus in the areas related to earth or environmental sciences [22].…”
Section: Introductionmentioning
confidence: 99%
“…As an educational method, PBL has been gaining ground and many studies point out several advantages: student satisfaction [28], ability to integrate new information into previous knowledge [29], a greater ability to transfer concepts to new problems [30], better results [31], development of various general skills [32], increasing student attitudes and interest in a STEM career [33], providing more opportunities for students' collaboration, and, thus, promoting higher-order thinking skills [5] and enhancing student achievement [34], among others. In broader studies, literature reviews and meta-analyses reported positive reactions to the methodology [35], gains in attitudes [36], and retention of knowledge for longer periods of time compared to the traditional methodology [37], increasing articulation compared to other active learning strategies [20], but not always better academic results [38]. In a recent systematic bibliometric review, Hallinger [20] analyzed about 12,000 Scopus-index documents published for 45 years (1974-2019), and concluded that there was a clear growth in PBL-related documents (57%) in the last decade (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), showing that there is greater academic interest in this subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem-based learning (PBL) is considered "one of the most popular student-centered pedagogies in use today" in higher education (1). Despite widespread PBL research in undergraduate education (2)(3)(4), this is a relatively unknown field at the high school level (5). Some evidence concerning its benefits have been reported (6,7), as in Biology (8,9) and Chemistry (10) education.…”
Section: Introductionmentioning
confidence: 99%